Positive and negative regulation of c-Myb by cyclin D1, cyclin-dependent kinases, and p27 Kip1 - Lei, Wanli (© 2005 by The American Society of Hematology, 2005)
The c-Myb transcription factor controls differentiation and proliferation in hematopoietic and other cell types and has latent transforming activity, but little is known about its regulation during the cell cycle. Here, c-Myb was identified as part of a protein complex from human T cells containing the cyclin-dependent kinase (CDK) CDK6. Assays using model reporter constructs as well as endogenous target genes showed that the activity of c-Myb was inhibited by cyclin D1 plus CDK4 or CDK6 but stimulated by expression of the CDK inhibitors p16 Ink4a, p21 Cip1, or p27 Kip1. Mapping experiments identified a highly conserved region in c-Myb which, when transferred to the related A-Myb transcription factor, also rendered it responsive to CDKs and p27. The results suggest that c-Myb activity is directly regulated by cyclin D1 and CDKs and imply that c-Myb activity is regulated during the cell cycle in hematopoietic cells.